Partisipasi Publik : Peran Inspiratif Kepemimpinan Jenderal Sudirman Dalam Kekuatan Bangsa Indonesia: Peran Inspiratif Kepemimpinan Jenderal Sudirman dalam Kekuatan Bangsa Indonesia - Wisang, Rumbha (LPPM Stikosa-AWS, 2024)
This research aims to provide an overview of the struggle of the heroes of the Indonesian nation, namely GeneralSoedirman, in maintaining Indonesia's dependence using a research method approach with literature studiesfrom history books, articles and analyzes that examine Soedirman's role and role. leadership in Indonesianhistory, interpretations and existing views, the results of this research state that General Soedirman received amodern education starting from his military experience, the war that united the Indonesian nation and became anintermediary for Indonesia's independence from colonialism. General Soedirman's struggle should be used as anexample of his own struggle, even though there are obstacles such as conflict in achieving certain goals. With hisdedication shown in strengthening the nation's strength against invaders,In conclusion, community participationhas an active role in supporting Indonesia's struggle. General Soedirman's leadership style is a reference as wellas an intangible legacy for the TNI because he has a character who is able to direct members, with his highdedication to Indonesia becoming an inspirational story for the community in facing current challenges.